Misretrieval but not misrepresentation: A feature misbinding account of post-interpretive effects in number attraction - Dempsey, Jack; Christianson, Kiel; Tanner, Darren (Quarterly Journal of Experimental Psychology, 2021)
Attraction effects in comprehension have reliably shown a grammaticality asymmetry in which mismatching plural attractors confer facilitatory interference for ungrammatical verbs, but no processing cost for grammatical verbs. While this has favoured cue-based retrieval accounts of attraction phenomena in comprehension, Patson and Husband offered offline evidence suggesting that comprehenders systematically misrepresent number information in attraction phrases, leaving open the possibility for faulty noun phrase (NP) representations later in processing. The current study employs two self-paced reading discourse experiments to test for number attraction misrepresentations in real time. Specifically, the attraction phrases occurred as embedded direct object phrases, allowing for a direct test of the role of attractor noun number in head noun number misrepresentation (i.e., no number cue from verb). Although no online evidence for misrepresentation was found, a third single-sentence rapid serial visual presentation experiment showed error rates to offline probes corroborating the post-interpretive findings from Patson and Husband, suggesting that a search in memory for associative features may not employ the same processes as the formation of dependencies in discourse comprehension. The findings are discussed in the framework of feature misbinding in memory in line with recent post-interpretive accounts of offline comprehension errors.